E-LEARNING DEVELOPMENT BASED ON MOODLE V.3.1. TO IMPROVE CONCEPT UNDERSTANDING OF LEARNING AND TEACHING COURSE - Anangga Widya Pradipta; Amy Nilam Wardathi (Universitas Muhammadiyah Semarang, 2018)
This study aims to produce internet-assisted learning media. Specifically this study aims to design and develop Moodle V.3.1 based e-learning. to improve the understanding of the concepts of the Learning and Learning course of the Health and Recreation Education Study Program of IKIP Budi Utomo Malang. The step taken is to use a development procedure which is a combination of the development procedures of Alessi and Trollip which includes 4 main stages namely planning, design, development and summative evaluation. The results of e-learning product development in the form of online learning management withMoodle version 3.1 application software with version 3.5.2 revision with the address https://widyapradipta.com. Feasibility of e-learning products in the aspect of material got a score of 76.34% and included in the good category, in the aspect of the media got a score of 81.83% and included in the excellent category, the response aspect of students got 88% in the good category and understanding of the concept students increased 23.6% to 83.6% in the very good category. Keywords: E-learning, Moodle V.3.1, Concept Understanding